Exploration of challenges in managing diversified workforce in Bangladesh during the COVID-19 Pandemic - Anjum, Nowshin (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.